The Influence of Leadership Style and Organizational Culture on Employee Performance through Work Motivation as an Intervening Variable (Economic Education Analysis Journal, 2022)
The purpose of this study was to determine the effect of leadership style and organizational culture on employee performance through work motivation as an intervening variable at the Education and Culture Office of Pesisir Selatan district. Methods of collecting data used survey and distributing questionnaires with a sample of 48 employees. The analytical method used Structural Equation Modeling (SEM) with Partial Least Square (PLS) 3. The results of data analysis concluded that leadership style had a positive and significant effect on work motivation; organizational culture had a positive and significant effect on work motivation; leadership style had a positive and significant effect on employee performance; organizational culture had no significant effect on employee performance; work motivation had a positive and significant effect on employee performance; work motivation could mediate the influence of leadership style on employee performance; and work motivation could mediate the influence of organizational culture on employee performance.